Pemberdayaan Masyarakat Melalui Kegiatan Pelatihan Hidroponik Yang Bernilai Ekonomis Bagi Masyarakat Desa Malabar Kabupaten Serang, Banten - Toni Anwar Mahmud; Caca Afrianisa; Muhammad Arif; Maulana Yusup; Aryanti Dwi Untari (Indonesian Journal Publisher, 2025)
Malabar Village, located in Bandung District, Serang Regency, is mostly utilized for settlements, agriculture, and plantations. With agricultural land becoming increasingly scarce, there is an urgent need for alternative farming methods. Hydroponics, a technique of growing plants without soil, offers a cost-effective and practical solution, especially for areas with limited land availability. The method of implementing this training activity begins with socialization activities about hydroponics, then continued with training activities and assistance in making hydroponics. Based on the results of the activities that have been carried out, there is a very good response from the residents. Although the residents are not familiar with the cultivation of plants with hydroponics using plastic bottles. Farming techniques such as hydroponics are new to the people of Malabar Village. This is because the people of Malabar Village are accustomed to farming or gardening conventionally or using soil planting media. Residents who are accustomed to farming traditionally welcome this new way. This project demonstrates that hydroponic farming is not only feasible but also affordable, requires minimal resources and offers potential economic benefits. This community empowerment activity was successfully implemented. After being given an understanding of the utilization of plastic bottle waste as a hydroponic growing medium, it can be seen that the skills and abilities of the community have increased in utilizing used bottles into hydroponic growing media, the equipment needed is easy, the manufacturing is simple, and the costs required are cheap. This activity supports the independence of residents in handling plastic bottle waste to be used as useful and valuable hydroponic planting media.